Transvaginal ultrasound compared with serum β-hCG level for diagnosis of ectopic pregnancy in symptomatic patients - Jeddi, Somayeh Zeynizadeh; Mobaraki, Noushin; Pirzadeh, Akbar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ultrasonography (US) is the most important imaging modality in detecting both intrauterine and ectopic pregnancies. The aim of this study was to comparison transvaginal ultrasound with serum β-hCG level for diagnosis of ectopic pregnancy (Ep) in referred women to Ardabil city hospital. Methods: In this cross-sectional study, a total of 207 women with diagnosis of Ep were enrolled during 2018. All women underwent transvaginal US in the first 24 hours and US done by an expert radiologist. Serum levels of β-hCG at first 24 hours and the time gap between US examination and last menstrual period (LMP) were compared between women with positive and negative US findings. Data collected by a checklist and analyzed by statistical method in SPSS version 21. Results: The primary US were positive in 174 women (84.1%) and negative in 33 women (15.9%). The mean of time gap between US and LMP in women with diagnosed EP was significantly higher than other women (median, 42 days versus 45 days, p=0.042). Also, the mean of serum level of β-hCG had significant difference between two groups. In logistic regression analysis results showed that the time gap between US and LMP hadn’t significant impact on EP diagnosis. The best discriminative zone was set at a serum β-hCG level of 105.65 mIU/ml with a sensitivity and specificity of 82% and 27%, respectively and the under-ROC area was 58%. Conclusions: According to our findings, the median serum level of β-hCG in women with undiagnosed Ep were significantly lower than women with correct diagnosis of Ep but the mean and median of time gap between US and LMP in women with diagnosed EP was more than women without Ep. Also, the proposed discriminative zone for serum level of β-hCG in our study is different from the previous studies.